Cryptic species inside the genus Hariotina (Scenedesmaceae, Sphaeropleales), with descriptions of four new species in this genus. Issue 4 (1st October 2020) - Wang, Qinghua; Liu, Xudong; Li, Shuyin; Xiong, Qian; Hu, Zhengyu; Liu, Guoxiang
ABSTRACT: The genus Hariotina was established in 1889 based on the type species Hariotina reticulata . This species was then transferred to Coelastrum by Senn (1899). The genus Hariotina was eventually restored by Hegewald et al . (2002) based on morphological characteristics. Species of Hariotina are ubiquitous in fresh water, especially in some tropical and subtropical areas. The taxonomic position of the genus is now considered to be within the family Scenedesmaceae. However, until now, there was an insufficient understanding of the molecular diversity within this genus, and the related reference sequences in the database were inadequate to resolve the species taxonomy. In this study, 20 strains of Hariotina were identified and successfully cultured in the laboratory. We used a combined approach, joining molecular and morphological analyses, to determine their taxonomic relationships and phylogenetic positions. The molecular analyses based on 18S rDNA+ITS sequences and the tuf A gene resolved the analysed strains into at least six species, including the known species H. reticulata and H. polychorda and four new species herein described, i.e. H. hainanensis sp. nov., H. compacta sp. nov., H. guilinensis sp. nov. and H. laxa sp. nov. The genus Hariotina was confirmed in the Scenedesmaceae as a monophyletic clade that was closely related to the genus Coelastrum in tuf A gene phylogeny. Strains with H. reticulata morphotype were found to be located on two different branches, and formed sister relationships with the other two morphologically distinct species. In addition, the topology was supported by all three DNA markers. The congruence between the phylogeny and the classical taxonomic system based on morphological criteria for this taxon is discussed.